Perception of Health Insurance Uptake Among University Students. - Sandra Catherine. O. Ingima (Uganda Christian University, 2022)
The purpose of the study was to assess perception of health insurance uptake among university students a case study of students undertaking a degree of business administration from the year 2:1 to 3:2 at Uganda Christian University Mukono. The study was guided by the following research questions; determine the effect of awareness levels among students regarding the health insurance packages available to them. To find out the extent to which income affects the uptake of health insurance among students. To determine how attitude affect the uptake of health insurance. To determine how government policies influence the uptake of private health insurance in. To find out whether students’ gender has an influence on uptake of health insurance. The study used a case study of students undertaking a degree of business administration from the year 2:1 to 3:2 at Uganda Christian University Mukono. The total population targeted for the study was 403.110 students from BBA 3:1, 103 from BBA 3:2, 162 from BBA 2:2 and 28 form BBA 2:1. Primary data was collected using structured questionnaires. Quantitative data was analyzed and the output was presented using a descriptive statistic of percentages. Qualitative data was analyzed and the output was presented by narration. The respondents agreed that health insurance is important and at a point beneficial for their future wellbeing, but however think it is a risk investment. Many believe it has difficult and undefined processes and also very expensive which makes it hard to maintain. Therefore this study concludes that many university students enjoy having health insurance not from their packets but that of their parents/ guardian and allowances from workplace.
This is a dissertation.